Bedside prediction of right subclavian venous catheter insertion length - Yoon Ji Choi; Kyung-Don Hahm; Koo Kwon; Eun-Ho Lee; Young Jin Ro; Hong Seuk Yang (Brazilian Journal of Anesthesiology, 2014)
Background and objective: The present study aimed to evaluate whether right subclavian vein (SCV) catheter insertion depth can be predicted reliably by the distances from the SCV insertion site to the ipsilateral clavicular notch directly (denoted as I-IC), via the top of the SCV arch, or via the clavicle (denoted as I-T-IC and I-C-IC, respectively). Method: In total, 70 SCV catheterizations were studied. The I-IC, I-T-IC, and I-C-IC distances in each case were measured after ultrasound-guided SCV catheter insertion. The actual length of the catheter between the insertion site and the ipsilateral clavicular notch, denoted as L, was calculated by using chest X-ray. Results: L differed from the I-T-IC, I-C-IC, and I-IC distances by 0.14 ± 0.53, 2.19 ± 1.17, and −0.45 ± 0.68 cm, respectively. The mean I-T-IC distance was the most similar to the mean L (intraclass correlation coefficient = 0.89). The mean I-IC was significantly shorter than L, while the mean I-C-IC was significantly longer. Linear regression analysis provided the following formula: Predicted SCV catheter insertion length (cm) = −0.037 + 0.036 × Height (cm) + 0.903 × I-T-IC (cm) (adjusted r2 = 0.64). Conclusion: The I-T-IC distance may be a reliable bedside predictor of the optimal insertion length for a right SCV cannulation. Resumo: Justificativa e objetivo: O presente estudo teve como objetivo avaliar se a profundidade de inserção de cateter em veia subclávia (VSC) direita pode ser prevista de forma confiável pelas distâncias do local de inserção na VSC até a incisura clavicular ipsilateral (I-IC), passando diretamente pela parte superior do arco da VSC ou da clavícula (denominadas I-T-IC e I-C-IC, respectivamente). Método: No total, 70 cateterismos de VSC foram estudados. As distâncias I-IC, I-T-IC e I-C-IC de cada caso foram mensuradas após a inserção do cateter guiada por ultrassom. O comprimento do cateter entre o local de inserção e a incisura clavicular ipsilateral (L) foi calculado por meio de radiografia. Resultados: As diferenças em centímetros de L em relação às distâncias I-T-IC, I-C-IC e I-IC foram de 0,14 ± 0,53; 2,19 ± 1,17 e 0,45 ± 0,68 respectivamente. A média de I-IC foi significativamente menor que L, enquanto a média de I-C-IC foi significativamente maior. A análise de regressão linear forneceu a seguinte fórmula: Comprimento previsto da inserção de cateter em VSC (cm) = −0,037 + 0,036 x Altura (cm) + 0,903 x I-T-IC (cm) (r2 ajustado = 0,64). Conclusão: A distância I-T-IC pode ser um preditivo confiável do comprimento de inserção ideal para canulação em VSC direita. Keywords: Central venous catheter, Clavicular notch, Subclavian vein, Palavras-chave: Cateter venoso central, Entalhe clavicular, Veia subclávia